Perancangan Mesin Pres Kaleng Minuman Untuk Mengurangi Volume Limbah Kemasan Minuman Kaleng - Yunia Dwie Nurcahyanie; Yitno Utomo; Djoko Adi Walujo; Rusdiyantoro Rusdiyantoro; Gilang Surya (Etos : Jurnal Pengabdian Masyarakat, 2022)
Many processes in the industry that were originally done by humans are now being replaced by machines. This community service is focused on helping SMEs to collect aluminum beverage cans. The purpose of this service is for the efficiency of human labor and the effectiveness of the completion time of the can pressing process. The service of this lecturer is to plan, manufacture, and test semi-automatic press machines to automate the movement of press machines. The method in designing this machine is an observation and observation study. From the design carried out, a semi-automatic pressing machine is produced, with the following specifications with a compressive power capacity of 150 kg. The electric motor used has a power of 0.5 PK and a rotation of 1400 rpm. Productivity has increased by 550%, before being pressed one box holds 36 cans, after being pressed it can accommodate 198 cans. Abstrak Banyak proses di industri yang semula dikerjakan manusia, sekarang mulai digantikan oleh mesin. Pengabdian masyarakat ini difokuskan untuk membantu UKM pengepul kaleng minuman berbahan aluminium. Tujuan pengabdian ini adalah untuk efisiensi tenaga manusia dan efektifitas waktu penyelesaian proses pengepressan kaleng. Pengabdian dosen ini adalah merencanakan, membuat, dan menguji mesin pres semi otomatis untuk keperluan otomatisasi penggerakan mesin pres. Metode dalam perancangan mesin ini adalah studi observasi dan pengamatan. Dari perancangan yang dilakukan, dihasilkan suatu mesin pres semi otomatis, dengan spesifikasi sebagai berikut kapasitas daya tekan dengan kekuatan pengepresan 150 kg. Motor listrik yang digunakan memiliki daya 0,5 PK dan putaran 1400 rpm. Produktivitas mengalami peningkatan 550%, sebelum di press satu box menampung 36 kaleng, setelah di press mampu menampun 198 kaleng.